Characteristics of Intimate Partner Violence in China: Gender Symmetry, Mutuality, and Associated Factors - Chen, Mengtong (Journal of interpersonal violence, 2021)
The primary research focus on female victims of intimate partner violence (IPV), coupled with a lack of discussion on mutual violence between intimate partners, has affected our understanding of IPV in China. In the current study, we aim to examine gender symmetry and mutuality in IPV in China. We also produce the first age-specific and gender-specific prevalence estimates for different types of IPV. The associations between IPV, demographic factors, personal factors, and relationship factors are also examined. We analyzed a set of data from 7,466 households in six regions in China collected between 2009 and 2010. Three-way cross-tab analyses and multinomial logistic regressions were performed to examine the prevalence of IPV in the preceding year by gender and age groups and its associations with different individual and relationship factors, respectively. For sexual violence and severe physical assault and injury, most victims experienced unidirectional violence. For psychological aggression and minor physical assault, mutual violence was more likely to occur among intimate partners. Gender symmetry was found in regard to physical assault and psychological aggression. There is gender asymmetry in sexual violence between Chinese intimate partners. Older individuals are less likely to be victims or perpetrators of IPV or to be involved in mutual violence. Factors associated with IPV show that mutual violence is generally analogous to violence perpetration. To prevent IPV, it is important to understand gender symmetry and mutuality of IPV in China. We need to involve both men and women in violence prevention and develop age-appropriate programs in the future.